Advanced G‐CSF‐producing non‐small cell lung cancer‐not otherwise specified, with favourable response to pembrolizumab monotherapy. Issue 7 (16th July 2020) - Matsui, Yohei; Yamada, Tadaaki; Masuzawa, Naoko; Hamada, Shinshichi; Takayama, Koichi; Hiranuma, Osamu
Abstract: Advanced granulocyte colony‐stimulating factor (G‐CSF)‐producing lung tumours are generally refractory to platinum‐based chemotherapy and are associated with poor prognosis. However, therapeutic strategies for these tumours remain unknown. A 74‐year‐old man was diagnosed with non‐small cell lung cancer‐not otherwise specified (NSCLC‐NOS); the clinical stage was T4N0M1c stage IVb. Blood testing showed leucocytosis and aberrant G‐CSF expression. We chose single‐agent pembrolizumab as the initial treatment because PD‐L1 was highly expressed in the tumours. A clinically favourable response was achieved from seven courses of pembrolizumab with a total disease‐free survival of 10 months. During this period, the blood leucocyte count was concordant with the disease condition. These observations showed that pembrolizumab monotherapy may be an effective treatment for patients with advanced G‐CSF‐producing NSCLC‐NOS and that the monitoring of leucocyte count may be a useful biomarker for predicting the efficacy of pembrolizumab monotherapy. Abstract : Here, we report a patient with non‐small cell lung cancer‐not otherwise specified (NSCLC‐NOS) with high PD‐L1 expression and aberrant granulocyte colony‐stimulating factor (G‐CSF) production, in whom monotherapy with the anti‐PD‐1 antibody pembrolizumab was effective as an initial treatment.